First record of Triatoma longipennis, Usinger, 1939 (Hemiptera: Reduviidae: Triatominae) in Tecozautla, Hidalgo - Nancy Rivas; Alberto Antonio-Campos; Julio Noguez-García; Ricardo Alejandre-Aguilar (Revista da Sociedade Brasileira de Medicina Tropical, 2023)
ABSTRACT Background: We report the presence of Triatoma longipennis for the first time in two localities in Hidalgo, Mexico. Methods: This study was conducted at Tecozautla municipality, Hidalgo. Collection was performed in April 2022. Results: We collected eight triatomines from Guadalupe: two fourth-instar nymphs, three fifth-instar nymphs, one female, and two males. In San Miguel Caltepantla, a female was collected inside a dwelling. One sample tested positive for Trypanosoma cruzi. Conclusions: These findings suggest the need to investigate the dynamics of this species with respect to the inhabitants of the study area.